Computational Analysis of Fit Between Human Head Shapes and Taekwondo Headgear - Muhammad Adham bin Azman (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Taekwondo headgear is required equipment for athletes to use in order to compete in any tournament. The headgear is used to lessen the impact of any hit from the opponent. Wearing inadequate headgear can result in a variety of injuries, the most serious of which is unconsciousness. These studies will conduct a 3D anthropometric investigation of the head and face, as well as an analysis of the Helmet Fit Index (HFI) score, in order to determine the suitability of the taekwondo headgear for Malaysian citizens. The research becomes precise and more accurate when using an analytical approach such as software gap analysis and 3D scanning because it is measured in a larger significant number. The results showed that current taekwondo heads produced by manufacturers have a lower fitness level than Malaysian citizen heads. It also shows that some areas of the helmet have less than 20% fitness, particularly in the front and back of the helmet. The findings could be used as data or information to design new taekwondo headgear in the future. This study could also serve as a model for future researchers who want to conduct fitness tests on other headgear using a similar method.